2008
DOI: 10.1051/agro:2008012
|View full text |Cite
|
Sign up to set email alerts
|

Yield potential and land-use efficiency of wheat and faba bean mixed intercropping

Abstract: -In Ethiopia, food production for a rapidly growing population from a continually shrinking farm size is a prime developmental challenge. Rising input costs, decline in soil quality, and buildup of insect pests, diseases and weeds have threatened the ecological and economic sustainability of crop production. To address those issues, intercropping of cereals with pulse crops could increase total grain production, provide diversity of products, stabilize yield over seasons, reduce economic and environmental risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 20 publications
7
66
1
3
Order By: Relevance
“…Grain total LER showed higher variability ranging from 0.92 to 1.26. These values were in line with other studies carried out on cereal-legume intercrops (Agegnehu et al 2008;Chu et al 2004;HauggaardNielsen et al 2006). Grain total LER less than 1 indicated that there was not always complementarity in the use of growth resources and that intraspecific and interspecific competition occurred between components.…”
Section: Calculation and Statisticssupporting
confidence: 93%
“…Grain total LER showed higher variability ranging from 0.92 to 1.26. These values were in line with other studies carried out on cereal-legume intercrops (Agegnehu et al 2008;Chu et al 2004;HauggaardNielsen et al 2006). Grain total LER less than 1 indicated that there was not always complementarity in the use of growth resources and that intraspecific and interspecific competition occurred between components.…”
Section: Calculation and Statisticssupporting
confidence: 93%
“…It is defined as the simultaneous growth of two or more species in the same field for a significant period of time (Willey 1979a) but without necessarily sowing or harvesting at the same time (Vandermeer et al 1998;Malézieux et al 2009). Niggli et al (2009) describe intercropping as an eco-functional intensification practice which has been widely used to boost crop productivity (Qin et al 2013), increase the land utilization ratio (Agegnehu et al 2008) and emit significantly lower amounts of greenhouse gases compared to sole crops (e.g. Oelhermann et al 2009;Naudin et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, one of the methods employed for producing medicine forage is to intercrop useful medicinal plants with predominant forage plants (Safikhani et al, 2014). Intercropping is an old and widespread practice used in many areas of the world (Lithourgidis et al, 2011) that may provide a balanced diet, reduce labor peaks, minimize adverse effects of biotic and abiotic factors, protect soil against erosion, improve the use of limited resources, increase stability of yield and provide higher outputs (Agegnehu et al, 2008). Girma (2015) reported that biological yield of corn was significantly affected by different intercropping systems and compared to sole maize decreased biological yield.…”
Section: Introductionmentioning
confidence: 99%